Evaluating a team-based approach to research capacity building using a matched-pairs study design - Holden Libby; Pager Susan; Golenko Xanthe; Ware Robert S; Weare Robyn (BMC Family Practice, 2012)
Abstract Background There is a continuing need for research capacity building initiatives for primary health care professionals. Historically strategies have focused on interventions aimed at individuals but more recently theoretical frameworks have proposed team-based approaches. Few studies have evaluated these new approaches. This study aims to evaluate a team-based approach to research capacity building (RCB) in primary health using a validated quantitative measure of research capacity in individual, team and organisation domains. Methods A non-randomised matched-pairs trial design was used to evaluate the impact of a multi-strategy research capacity building intervention. Four intervention teams recruited from one health service district were compared with four control teams from outside the district, matched on service role and approximate size. All were multi-disciplinary allied health teams with a primary health care role. Random-effects mixed models, adjusting for the potential clustering effect of teams, were used to determine the significance of changes in mean scores from pre- to post-intervention. Comparisons of intervention versus control groups were made for each of the three domains: individual, team and organisation. The Individual Domain measures the research skills of the individual, whereas Team and Organisation Domains measure the team/organisation's capacity to support and foster research, including research culture. Results In all three domains (individual, team and organisation) there were no occasions where improvements were significantly greater for the control group (comprising the four control teams, n = 32) compared to the intervention group (comprising the four intervention teams, n = 37) either in total domain score or domain item scores. However, the intervention group had a significantly greater improvement in adjusted scores for the Individual Domain total score and for six of the fifteen Individual Domain items, and to a lesser extent with Team and Organisation Domains (two items in the Team and one in the Organisation domains). Conclusions A team-based approach to RCB resulted in considerable improvements in research skills held by individuals for the intervention group compared to controls; and some improvements in the team and organisation's capacity to support research. More strategies targeted at team and organisation research-related policies and procedures may have resulted in increased improvements in these domains.